KOMPARASI PEMBERIAN HEXADOL DAN CHLORHEXIDINE SEBAGAI ORAL HYGIENE TERHADAP PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) - Hadi Kusuma Atmaja (Jurnal Kesehatan Prima, 2014)
Abstract: Patients in critical care unit inserted by ventilators could potentially develop complications as known by Ventilator Associated Pneumonia (VAP). The preventions of VAP include non-pharmacological and pharmacological intervention. Pharmacological prevention of  VAP is the use of antiseptic drug in oral hygiene procedure. Kinds of anticeptic drugs are hexadol (hexetidine) and chlorhexidine. The purpose of this study was to evaluate the effects of oral hygiene with hexadol and chlorhexidine in patients with mechanical ventilator in ICU. The study was a quasi-experiemntal two group design. There were 30 subjects recruited by purposive sampling in the ICU at Pantiwilasa hospitals on street Dr. Cipto and Citarum Semarang. The subjects were divided randomly into 2 groups: 15 subjects given by hexadol 0,1% and 15 subjects given by chlorhexidine 0,2% for twice a day. VAP was assessed by Clinical Pulmonary Infection Score(CPIS).                    The results show that CPIS ≤ 5 was no VAP at 96,67% and ≥ 6 was VAP at 3,33%. There was no significant difference between oral hygiene with hexadol and chlorhexidine (U=78; p<0,14). Oral hygine with hexadol twice a day was as effective as oral hygiene with chlorhexidine to prevent VAP.